Oral antigen exposure in extreme early life in lambs influences the magnitude of the immune response which can be generated in later life - Buchanan, Rachelle M (BioMed Central, 2013)
BACKGROUND: Previous investigations in newborn lambs determined that adenovirus-mediated expression of antigen to a localized region of the gut induced antigen-specific mucosal and systemic immunity. These experiments were limited in that the localized region of the gut to which antigen was introduced was sterile and the influence of colostrum on the antigen was not assessed but they do suggest that mucosal vaccines may be an effective vaccination strategy to protect neonatal lambs. We propose that persistent oral antigen exposure introduced in extreme early life can induce immunity in lambs, despite the presence of commensal bacteria and colostrum. RESULTS: To test this hypothesis, conventionally raised newborn lambs (n = 4 per group) were gavaged with ovalbumin (OVA) starting the day after birth for either a single day (2.27 g), every day for 3 days (0.23 g/day), or every day for 3 days then every second day until nine days of age (0.023 g/day). Lambs gavaged with OVA for 3 to 9 days developed significant serum anti-OVA IgG titres (p < 0.05), but not IgA titres, relative to control lambs (n = 4) after 3 and 4 weeks. At 4 weeks of age, lambs were immunized with OVA in Incomplete Freund’s Adjuvant via intraperitoneal (i.p.) injection then lambs were euthanized at 7 weeks. Serum anti-OVA IgG titres were further augmented after i.p. immunization indicating immunity persisted and tolerance was not induced. Serum IgA titres remained low regardless of treatment. It is known that i.p. priming of sheep with antigen in Freund’s complete adjuvant leads to an enhanced number of IgA and IgG antibody containing cells in the respiratory mucosa (Immunology 53(2):375–384, 1984). Lambs gavaged with a single bolus of 2.27 g OVA prior to i.p. immunization showed very low titres of anti-OVA IgA in the lung lavage. These data suggest that a single, high dose exposure to OVA can promote tolerance which impacts response to systemic vaccination in later life. Lambs gavaged with 0.023 g OVA for 9 days (Group C) generated significant anti-OVA IgA titres in lung (p < 0.001) compared to negative control lambs but no additive effect was observed compared to parenteral control lambs. When splenocytes were re-stimulated with OVA ex vivo, all groups failed to show increased lymphocyte proliferation or interferon (IFN)-γ production relative to the parenteral control group. CONCLUSIONS: In agreement with our hypothesis, persistent low dose antigen exposure primes humoral antibody production in serum in conventionally raised newborn lambs. In contrast, a single high dose bolus of antigen triggered oral tolerance which negatively impacted the quality and magnitude of the immune response to i.p. immunization in later life. These tangential responses are important as they indicate that the dose and/or repeated oral exposure to antigen, such as that which may be found in the neonate’s environment, may promote immunity or alternatively it may negatively impact responses to parenteral vaccination.